The Effect of Hospital Management Information System and Good Clinical Governance on The Effectiveness of Health Services with Internal Control as A Moderating Variable at Hikmah Hospital, Makassar - Nurul Auliah; Marwah Yusuf; Dahniyar Daud (Faculty of Economics dan Business, Atma Jaya Makassar University, 2026)
This study aims to examine the influence of hospital management information systems and good clinical governance on the effectiveness of health services with internal control as a moderating variable at Hikmah Makassar Hospital. The population in this study was all employees of the Hikmah Hospital in Makassar City totaling 173 employees. Meanwhile, in determining the sample, we used several sample determination criteria so that the total sample in this study was 77 respondents. This research uses primary data by conducting direct research in the field, by giving questionnaires/statement sheets to 77 respondents. The data analysis method used is intervening analysis with the help of the Smart PLS application. Research results show that: partially that: Hospital Management Information Systems have a positive and significant effect on the effectiveness of health services in hospitals. Good Clinical Governance has a positive and significant effect on the effectiveness of health services in hospitals. Internal Control is able to moderate the Hospital Management Information System on the effectiveness of health services at the Hospital and Internal Control is able to moderate Good Clinical Governance on the effectiveness of health services in hospitals.